Model to localize gauge and tensor fields on thick branes - Chumbes, A. E. R. [UNESP]; Hoff da Silva, J. M. [UNESP]; Hott, M. B. [UNESP] (Amer Physical Soc, 2012)
It is shown that the introduction of a suitable function in the higher-dimensional gauge field action may be used in order to achieve gauge bosons localization on a thick brane. The model is constructed upon analogies to the effective coupling of neutral scalar field to electromagnetic field and to the Friedberg-Lee model for hadrons. After that we move forward studying the localization of the Kalb-Ramond field via this procedure.